Breaking it Down: Economic Consequences of Disaggregated Cost Disclosures - Berger, Philip G.; Choi, Jung Ho; Tomar, Sorabh (Management Science, 2024)
Motivated by the Financial Accounting Standards Board’s project on the disaggregation of income statement expenses, we study a Korean rule change that allowed firms to withhold a previously mandated disaggregation of cost of sales (CoS). We find that after withholding, firms’ profitability increases by 1.6 percentage points. Our industry-focused results suggest that withholding affects profitability by reducing the transfer of competitive information to peer firms. We then document a range of evidence consistent with the idea that firms withhold disaggregated CoS to protect cost innovations from rivals. First, we construct a novel measure of firms’ cost-innovative potential and show that it predicts withholding and subsequent profitability gains under the voluntary disclosure regime. Second, we document efficiency gains following the withholding of disaggregated CoS. Third, our survey experiment of 1,257 U.S. public firm managers shows that they would reduce investments in process/cost innovations if they were required to disaggregate CoS. Our study highlights to standard setters and academics that CoS disaggregation entails operational consequences for firms. This paper was accepted by Brian Bushee, accounting. Funding: The authors acknowledge financial support from the University of Chicago Booth School of Business, the Stanford Graduate School of Business, and the Southern Methodist University Cox School of Business. Supplemental Material: The data files and online appendix available at https://doi.org/10.1287/mnsc.2023.4780 .